Hak Anak Usia Dini Dalam Sistem Ketatanegaraan di Indonesia - Yandy, Eza; Endah Karya Lestiyani, Tri; Sundari, Cici (Generasi Emas, 2024)
This study aims to determine the rights of early childhood in the constitutional system in Indonesia. This type of research is library research with a normative legal approach using data collection methods through a search of literature related to problems, laws and regulations, interviews and other references as research support. As for the results of this research, in principle the state through the government has made good efforts starting from the establishment of state institutions in Indonesia that are specifically engaged in protecting children, then formulating rules in fulfilling and guaranteeing children's rights in Indonesia, then protecting children are also accommodated in Law number 39 of 1999 concerning Human Rights articles 52 to article 66. In Indonesian Laws and Regulations, in principle, children's rights are guaranteed in them, including the rights of early childhood, early childhood gets special attention because holistic-integrative development is an effort to realize Indonesian children who are healthy, intelligent, cheerful and have noble character, while one of the indicators causing the loss of children's rights includes the crime of child exploitation.